An extensive study: to assess the changing trends in prevalence and development of TTIs in non-remunerated blood donors at a tertiary care teaching hospital in Central India - Dr. Roopam Jain; Dr. Preeti Jain; Dr. Mohit Kashiv; Dr. P. Desai; Dr. U. Chudgar; Dr. N. Choudhury; Dr. V.K. Mahadik (Tropical Journal of Pathology and Microbiology, 2018)
Background: Transfusion transmitted infections (TTI) are a major challenge to the transfusion services all over the world. The problem of TTIs is directly proportionate to the prevalence of the infection in the blood donor community which represents the general population. The purpose of this study is to analyze the status of Transfusion transmitted infections among seemingly healthy donors, targeting the non-remunerated blood donors (voluntary and replacement) during the period 2009- 2017.Material and method: A total of 84,975 blood donors were screened for seropositivity of HBsAg, anti-HCV, HIV, VDRL and malaria antigen at Regional blood transfusion center, in central India.Result: Out of 84,975 donations, 1906 (2.24%) were sero-reactive for five blood transmitted infections. Among these, prevalence of HIV was 0.067% (57 donors), seroprevalence of HBsAg was 1.39% (1184 donors), HCV showed 0.068% (58 donors), VDRL showed 0.66% (564 donors) and malaria had 0.05% prevalence (43 donors).Conclusion: HBV is the most common infection among voluntary blood donors, followed by Syphilis. Replacement donors have higher prevalence of TTIs in overall donor population. A change to voluntary blood transfusion service would reduce the chances of post transfusion infections.